Modelling and strength evaluation of masonry bridges using terrestrial photogrammetry and finite elements. (November 2016) - Stavroulaki, M.E.; Riveiro, B.; Drosopoulos, G.A.; Solla, M.; Koutsianitis, P.; Stavroulakis, G.E.
Abstract: Several numerical models are presented in this article, for the study of the ultimate behaviour of a real stone arch bridge. For the exact representation of the geometry an integral and comprehensive survey involving Terrestrial Photogrammetry and Ground Penetrating Radar is in order to provide a realistic 3D geometric model for the subsequent mechanical analysis of the bridge. The accuracy of the photogrammetric method permitted detecting cracks in different areas and the GPR completed the geometric model with information of hidden parts such as backfill, arch ring thickness, etc. Finite element analysis models, incorporating damage, elastoplasticity and contact, are then developed. Comparison between these models is considered in a single arch of the structure. The classical four hinges mechanism appears in the arch. A model of the whole structure, where the arch and the fill are taken into account, is finally developed. Results show how damage is developed in the body of the arch, for loadings that include forces, or vertical and transverse displacements in the supports.